Investing in fixer-uppers : a complete guide to buying low, fixing smart, adding value, and selling (or renting) high - DeCima, Jay P. (McGraw Hill, 2024)
"Nobody wants to buy an ugly, decrepit, rundown house--which is exactly why they provide real estate investors with the best bargains! In Investing in Fixer-Uppers, nationally known real estate guru Jay DeCima reveals how investors can add thousands of dollars to the value of an "ugly" house"--